1999
DOI: 10.1177/0273475399211003
|View full text |Cite
|
Sign up to set email alerts
|

Socialization-Based Approach to Predicting Retail Career Preference and Choice

Abstract: In this study, it was hypothesized that (1) four categories of retail career socialization (i.e., socialization related to education, work, retail establishments, and family) will predict three aspects of retail career preference (i.e., intrinsic, extrinsic, and lifestyle) and (2) retail career preference will, in turn, predict retail career choice. College juniors and seniors nationwide (N = 723) responded to a survey questionnaire. The findings indicated that socialization related to retail work and educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Career-driven learning is a process that is largely propelled not only by internal motivations but also by the support and acceptance of numerous publics (Shim et al, 1999). Most courses need the acceptance of the developed competences from employers and professional associations.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Career-driven learning is a process that is largely propelled not only by internal motivations but also by the support and acceptance of numerous publics (Shim et al, 1999). Most courses need the acceptance of the developed competences from employers and professional associations.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Therefore, it is necessary to provide adequate information, especially related to market needs for labor through social media [12]. Social media which currently become a lifestyle have influencedvarious sectors of life, including career decision making [4]. It is not surprising that any information provided by social media is sometimes swallowed up directly for making decisions.…”
Section: % 14% 13%mentioning
confidence: 99%
“…It is widely accepted that career selection process is also influenced by aspects of students' socialization with the surrounding environment and students' social structure as well as social structure in the environment around them [3]. In addition, family relationships and students' lifestyle are also considered influential in the career selection process that they carried out [4]. Later it was also identified that emotional intelligence also influences career decision-making and selection processes at least in terms of possessed values, interests and career aspirations [5].…”
Section: Introductionmentioning
confidence: 99%
“…tours for older adults, medical insurance for the journey and recreation-based travel). On the basis of socialization theory, the individual goes through a process of socialization, during which socialization agents positively influence cognitive and behavioral outcomes (Shim et al, 1999). A socialization agent is referred to as an important player in influencing the socialization process, such as family members, a school or an organization such as a retailer (Shim et al, 1999).…”
Section: Factors Influencing Online Shoppingmentioning
confidence: 99%
“…On the basis of socialization theory, the individual goes through a process of socialization, during which socialization agents positively influence cognitive and behavioral outcomes (Shim et al, 1999). A socialization agent is referred to as an important player in influencing the socialization process, such as family members, a school or an organization such as a retailer (Shim et al, 1999). Building upon the socialization theory, Shim et al (2005) have demonstrated that older adults' attitudes tend to be influenced by socialization agents such as friends.…”
Section: Factors Influencing Online Shoppingmentioning
confidence: 99%